The association between ABO blood type and outcomes following sudden cardiac arrest: a multicenter observational study - Jiun-Wei Chen; Ren-Jie Tsai; Cheng-Yi Fan; Cheng-Yi Fan; Sih-Shiang Huang; Sih-Shiang Huang; Ching-Yu Chen; Chi-Hsin Chen; Chi-Hsin Chen; Chi-Hsin Chen; Jia-How Chang; Jia-How Chang; et al. (Frontiers in Medicine)
BackgroundABO blood type has been associated with various disease outcomes, but its relationship with outcomes in patients with sudden cardiac arrest (SCA) remains unexplored.MethodsThis was a retrospective analysis of adult out-of-hospital cardiac arrest patients with SCA treated at three major branches of the National Taiwan University Hospital between January 2016 and July 2023. The variables examined for their possible influence on the neurological and survival outcomes of patients with SCA were sociodemographic characteristics, pre-existing diseases, resuscitation events, and blood type. The results of a multivariable logistic regression were reported as adjusted odds ratios (aORs) and 95% confidence intervals (CIs). Neurological outcomes were determined by the Cerebral Performance Category (CPC) scale at hospital discharge.ResultsNo significant differences were found in the prevalence of each blood type between those who survived and those who did not or between those with good (CPC 1–2) or poor (CPC 3–5) neurological outcomes. There was no significant association between survival and blood type; however, patients with blood type AB had a higher probability of good neurological outcomes than those with blood type O (aOR: 1.98, 95% CI: 1.02–3.83, p = 0.042). A sensitivity analysis of the data from patients with aseptic etiologies also showed a significantly higher likelihood of good neurological outcomes among those with blood type AB (aOR: 2.21, 95% CI: 1.12–4.35, p = 0.023).ConclusionABO blood type is not associated with survival in patients with SCA, but blood type AB is associated with better neurological outcomes than type O.